Strategi Pramusaji dalam Menangani Keluhan Pelanggan di Kori Restaurant - I Gusti Agung Bhisma; Kadek Ayu Ekasani (Lembaga Pengembangan Kinerja Dosen, 2025)
Kori Restaurant is the restaurants offering an authentic Balinese atmosphere with international cuisine and Asian flavours, as well as high quality service. Located at Poppies Lane II, Legian, Kuta, this restaurant is in a strategic location near the Beachwalk shopping centre and the bustling Kuta Beach area. In reality at this restaurant, customer complaints are often faced by restaurant staff, both complaints in online and offline media. The purpose of this study was to determine the waiter's strategy in handling customer complaints at Kori Restaurant. This research uses qualitative research with data collection techniques with observation, interviews and documentation, data validity techniques are used triangulation methods and with data analysis using data reduction methods, data presentation and conclusion drawing. The results of this study state that efforts to handle customer complaints at Kori Restaurant are identifying problems, listening to guest complaints and distinguishing between service or food complaints, handling is carried out according the type of complaint, and strategies carried out by Kori Restaurant waiters in handling customer complaints, namely listening to guest complaints without cutting the conversation, clarifying the problem, internal verification, and apologising and offering solutions such as replacing food or drinks with complimentary, as well as remaking orders if needed and offering discounts, or freeing problematic orders, and it can be concluded that the waiter's strategy in handling guest complaints at Kori Restaurant is listening, clarifying, internal verification, apologising and offering appropriate solutions.